RESTORATIVE JUSTICE IN SETTLEMENT OF MINOR CRIMES - Ilmuwani Lubis; Firman Halawa (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
According to the proponents of the value of justice, the law has been moving quickly and more sharply if legal cases are related to small people and question the interests of big people, including those with power. However, if there is a case that involves or is suspected of being the perpetrator, big people and powerful people, then the law seems to be paralyzed and dull. Apart from requiring legal certainty and justice, legal solutions must also have beneficial value, which is the current problem and challenge. namely, how to realize a law enforcement process that is able to fulfill legal objectives, namely achieving legal certainty that is just and useful. The method used in this research is a descriptive analytical method with a normative juridical main approach.Reforming criminal law must be carried out with a policy approach, because it is essentially part of a policy step or policy (i.e. part of legal politics/law enforcement, criminal law politics, criminal politics and social politics). Criminal justice is not just seen as a crime prevention system. , but is seen as a social problem that is the same as crime itself. The implementation of criminal sanctions needs to be linked to human development policies that want to form complete Indonesian people. The use of criminal sanctions imposed on violators must be in accordance with civilized human values. Apart from that, punishment is used to raise awareness among offenders of human values ​​and social values. Prioritizing peace through deliberation to reach consensus is an integral mechanism in the life of society in Indonesia. Legal reform in Indonesia cannot be separated from conditions. The objective of Indonesian society is to uphold the values ​​of religious law in addition to traditional law, so it is necessary to explore legal products that are sourced and rooted in cultural, moral and religious values. Settlement of ordinary criminal acts with minor motives can be achieved through penal mediation, called the restorative justice approach, which focuses on there is direct participation of perpetrators, victims and the community in interpreting criminal acts. Restorative justice is also a new framework of thinking that can be used in responding to criminal acts for law enforcers and workers in Indonesia.